GAMBARAN PENGETAHUAN REMAJA SISWI SMP TENTANG MAKANAN SIAP SAJI (FAST FOOD) YANG DAPAT MENYEBABKAN DISMENOREA - DEVYTA IS YULIANI, - (2023)
Fast food is defined as a type of food that contains lots of free radicals so that it can cause dysmenorrhoea in adolescents. Lack of knowledge about the content and impact contained in fast food causes adolescents to often consume these foods. This study aims to determine the picture of adolescent students' knowledge about fast food that can cause dysmenorrhoea at SMPN 2 Tanjungsiang. This study used a quantitative descriptive survey method involving 96 respondents with sampling using total sampling. The sample in this study was 96 female students aged 12-14 years. Data collection using questionnaires that were distributed directly with a number of questionnaires as many as 25 questions, then analyzed by presenting quantitative distribution data. The results of the study were almost half of 78 people (81%) in the good category, as many as 10 people (11%) in the sufficient category, and as many as 8 people (8%) in the less category. It can be concluded that the picture of knowledge at SMPN 2 Tanjungsiang is almost half in the good category. For teenagers who often consume ready-to-eat foods and have good knowledge, they are expected to apply it in everyday life that fast food is dangerous for health.